Pembelajaran Kontekstual sebagai Inovasi Kreatif dalam Menjadikan Materi Ajar Lebih Bermakna - Lulut Suhermi; Barokah, Novita; Rahmat Kamal (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
Education in Indonesia faces significant challenges in connecting teaching materials with students' real-life experiences. Learning content is often perceived as abstract and irrelevant to daily experiences, which can reduce student engagement and motivation in the learning process. Therefore, contextual learning emerges as an innovative solution that links instructional materials with students' life contexts. This study aims to explore the implementation of contextual learning as a creative approach to make teaching materials more meaningful and relevant. Using the Systematic Literature Review (SLR) method, this research analyzes various studies from accredited national journals and conference proceedings published between 2019 and 2024. The findings indicate that contextual learning can improve concept understanding, learning motivation, and active student engagement. Furthermore, this approach has proven effective in strengthening critical thinking and problem-solving skills. Based on these findings, it is recommended that contextual learning be more widely implemented in the education system to create more meaningful and relevant learning experiences for students.